Nanomaterial-Based Carbon Paste Electrodes for Voltammetric Determination of Naproxen in Presence of Its Degradation Products - Hassan A. M. Hendawy; Waheed M. Salem; Mahmmoud S. Abd-Elmonem; Elmorsy Khaled (Journal of Analytical Methods in Chemistry)
The present work describes a novel, simple, and fast electroanalytical methodology for naproxen (NAP) determination in pharmaceutical formulations and biological fluids in the presence of its degradation products. Carbon paste electrodes (CPEs) modified with different carbon nanomaterials, namely, glassy carbon powder (GCE), multiwall carbon nanotubes (MWCNTs), single-walled carbon nanotubes (SWCNTs), graphene nanosheets (Gr), and graphene oxides (GO) were tested. Comprehensive studies were performed on the electrode matrix composition including the nature of the pasting liquids, pH, carbon nanomaterials, and mode of electrode modification. Two anodic oxidation peaks were recorded at 0.890 and 1.18 V in 1 × 10−1 mol·L−1 phosphate buffer solution at pH 6. Oxidation of naproxen (NAP) is an irreversible diffusion-controlled process. Calibration plots were rectilinear in the concentration ranging from 0.067 to 1.0 µg·mL−1 with correlation coefficient 0.9979. Photodegradation of NAP resulted in disappearance of the oxidation peak at 1.18 V, allowing simultaneous determination of NAP in presence of its degradation product. The achieved high sensitivity and selectivity suggest the application of the proposed protocol for naproxen determination in pharmaceutical preparations and human blood plasma.